Psychological Impact on Children Due to the Decision of Acquittal of Child Abuse Crimes Linked to the Child Protection Law - Dian Widyaningrum; Yuniar Rahmatiar; Muhamad Abas (Warmadewa Press, 2024)
The rise in child molestation cases has brought significant concern due to the severe psychological and physical trauma inflicted on victims, particularly children. Such trauma can hinder their future growth and development. This study investigates the legal framework governing child molestation crimes and examines the psychological impact on children when perpetrators are acquitted, particularly in relation to the Child Protection Law. The research employs a normative legal method to analyze relevant laws, including both the Criminal Code and the Child Protection Law, which impose varying penalties based on the nature of the crime and the relationship between the offender and the victim. The results indicate that acquittal in molestation cases leads to prolonged psychological harm, increases the risk of physical issues such as sexually transmitted diseases, and can result in social stigmatization and exclusion. The study concludes that robust legal protection is essential for child victims, emphasizing the importance of ensuring their rights and providing appropriate remedies. Law Number 35 of 2014 on Child Protection underscores the state’s obligation to protect children from all forms of violence, including sexual violence.